How to support cooperative driving by HMI design?. (December 2019) - Kraft, Ann-Kathrin; Maag, Christian; Baumann, Martin
Abstract: Cooperative driving means that drivers coordinate their individual driving in a way that the involved drivers facilitate each others' goal achievement. In cooperation situations, like merging or turning left, one driver on a priority road generates a gap to help a driver on a minor road. This study aimed to investigate what kind of information should be provided to the driver via the Human-Machine-Interface (HMI) to support cooperative driving. Therefore, three different visual HMIs that vary in the type of information presented were developed to examine the drivers' information needs. The HMI focus either on the illustration of the partner and the gap, giving an advice how to drive, or the presentation of the current status of the advanced driver assistance system (ADAS). The results show that the acceptance, comprehensibility of and reliance in the ADAS for cooperative driving are highest when the HMI highlights the partner and gap. From the perspective of the 'cooperation granting' driver confirming explicitly a cooperation request and an advice how to generate the gap are perceived as helpful. This clearly indicates that the driver requesting cooperation prefers information about the situation, whereas the driver granting cooperation additionally appreciates support in how to execute the maneuver. Highlights: An HMI of an ADAS for cooperative driving is evaluated in a simulator study. The kind of information which should be provided to the driver is investigated. The acceptance of the ADAS is highest when the HMI highlights the partner and gap. When 'cooperation granting' an advice how to generate the gap is perceived as helpful.